Effect of 4 Mat Constructivist Model Using Electronic Educational Resources on Systemic Thinking and Learning of Artistic Performance of Some Freestyle Wrestling Holds for Students - Mohammed Hato Ali (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
The research aimed to identify the effect of the McCarthy (4Mat) model using electronic educational aids on systematic thinking and the learning of skilled performance for some wrestling holds among third-year students at the College of Physical Education and Sports Sciences, University of Masan. The researcher adopted an experimental research approach on (50) students from the College of Physical Education and Sports Sciences, University of Masan, who were divided into two groups: an experimental group and a control group, each consisting of (25) students. The McCarthy (4Mat) model was applied using electronic educational aids to the experimental sample students over (9) educational units, with one educational unit applied each week. Three educational units were allocated for each hold, applied on Thursdays at 8:30 am. The researcher found that the educational units based on the McCarthy (4Mat) constructivist model using electronic educational aids had an impact on learning the skilled performance of some wrestling holds. The experimental group students outperformed the control group students. Electronic educational aids (tablets and smart screens) played an effective role in learning the skilled performance of some wrestling holds, which was evident in the experimental group students who outperformed the control group students. The researcher recommended that it is necessary to use the McCarthy (4Mat) constructivist model in learning wrestling holds in physical education and sports science colleges because it has a good effect on learning the skilled performance of wrestling holds.